Serotonergic mechanisms of the lateral parabrachial nucleus on DOCA-induced sodium intake - De Gobbi, JIF; De Luca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2000)
It has been shown that the serotonergic mechanisms of the lateral parabrachial nucleus (LPBN) inhibit NaCl intake in different models of angiotensin II (ANG II)-dependent NaCl intake in rats. However, there is no information about the involvement of LPBN serotonergic mechanisms on NaCl intake in a model of NaCl intake not dependent on ANG II like deoxycorticosterone (DOCA)-induced NaCl intake. Therefore, in this study we investigated the effects of bilateral injections of serotonergic agonist and antagonist into the LPBN on DOCA-induced 1.8% NaCl intake in rats. Male Holtzman rats were treated with s.c. DOCA (10 mg/rat each every 3 days). After a period of training, in which the rats had access to 1.8% NaCI during 2 h for several days, the rats were implanted with stainless steel cannulas bilaterally into the LPBN. Bilateral injections of the serotonergic receptor antagonist methysergide (4 mug/0.2 mul each site) in the LPBN increased 1.8% NaCI intake (32.2+/-3.9 versus vehicle: 15.0+/-1.6 ml/2 h, n = 10) and water intake (11.5+/-3.5 versus vehicle: 3.2+/-1.0 ml/2 h). Injections of the serotonergic 5HT(2A/2C) receptor agonist DOI (5 mug/0,2 mul each site) in the LPBN reduced 1.8% NaCl intake (6.8+/-1.7 versus saline: 12.4+/-1.9 ml/2 h, n = 10) and water intake (2.2+/-0.8 versus saline: 4.4+/-1.0 ml/2 h). Besides the previously demonstrated importance for the control of ANG II-dependent water and NaCl intake, the data show that the serotonergic inhibitory mechanisms of the LPBN are also involved in the control of DOCA-induced NaCl intake. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: deoxycorticosterone; NaCl intake; water intake; 5HT; LPBN